Tinjauan Maqoshid Syariah Pada Produk Asuransi Syariah (Studi Komparatif pada Pru Syariah, dan Avrist) - Hamidah Farras Samah; Hilmy Fikri (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
This study aims to analyze the practice and application of sharia insurance in terms of maqashid sharia aspects. the sample used is Pru Syariah and Avrist which are private insurance institutions that have conventional business holdings. The method used is descriptive comparative, namely comparing product and service descriptions of the two insurance companies based on secondary data and then comparing them. the sharia standard reference is the syatibi version of maqoshid sharia which is measured normatively. The results of the study show that in general these two insurances have implemented the maqoshid sharia principles, namely protecting religion, life, property and offspring. only maintaining reason is still considered minimal, this is indicated by the understanding of sharia insurance agents about sharia law which is not yet sufficient which is feared to spread to the point of protecting religion.